Risk-adjusted return in sustainable finance: A comparative analysis of European positively screened and best-in-class ESG investment portfolios and the Euro Stoxx 50 index using the Sharpe Ratio - Julius Gardenier; Visieu Lac; Muhammad Ashfaq (IU Internationale Hochschule, 2021)
This discussion paper aims at describing the risk-adjusted return of European sustainable and conventional investment portfolios and comparing them to determine whether sustainable investment portfolios generate superior risk-adjusted returns. The paper is based on the bachelor thesis of Julius Gardenier. In fulfilling this aim, we actively construct sustainable positively screenedand best-in-class portfolios using the Sustainalytics ESG risk rating with the help of modern portfolio theory. In a second step, the Sharpe Ratios of these portfolios are compared with those of the Euro Stoxx 50, as a proxy for a conventional portfolio, for the time horizon between 2005 and 2019 thatis divided into ten instances on whose SharpeRatios paired sample t-tests are applied. Results show a statistically significant higher mean Sharpe Ratio for both types of sustainable portfolios when compared to the Euro Stoxx 50 for the periodunder investigation. Additionally, it was found that best-in-class portfolios yielded higher mean Sharpe Ratios. We conclude that, under reference to the paper's limitations, sustainable investments yielded superior risk-adjusted returns when compared to the conventional investment portfolio. Furthermore, the paper's findings identify recommendations for future research and may contribute to the growing body of academic literature in the field of sustainable finance.
Keywords: G11; Q56; 650; Sustainable finance; modern portfolio theory; Sharpe Ratio; ESG risk rating